Evaluation of rat model oral candidiasis mucosal response immune - Sulistyani, Erna; Triwahyuni, Iin Eliana; Harmono, Happy; Sholehah, Almaratus; Prameswari, Syefira Putri; Mayangsari, Zahra; Perwitasuci, Brigitta Damai; Wulandari, Widya Nurfitriastuti (Odonto : Dental Journal, 2023)
Background: The choice of antifungal drugs is limited and has not yet made significant progress. The animal model of oral candidiasis is a crucial factor in exploring antifungals. In our previous study's oral candidiasis rat model, we found an increase in the sedimentation rate and a decrease in infection microbiologically and histologically on day 8 compared to day five after inoculation. On the other hand, blood plasma levels of IL-17, as the main cytokine in fungal infections, keep at a low level. The study aims to prove the increase in the immune response in the oral mucosa of an oral candidiasis rat model on the 8th day after inoculation of C. albicans. Methods: The sample consisted of 2 groups; healthy Wistar rats as a control and Wistar Rat rats treated as an oral candidiasis rat model. Eight days after inoculating C. albicans,The immune response was evaluated by counting the number of visual field inflammatory cells on the dorsum of the rat dorsum tongue.Results: The number of inflammatory cells, including macrophages in the dorsal tongue mucosa of oral candidiasis rats, was higher than that of healthy rats. Conclusion: There was an increase in the number of inflammatory cells in the dorsum of the tongue mucosa of the oral candidiasis rat model on day 8, which is a sign of an increased immune response in the experimental animal model.